Pathogenicity of Salmonella Typhimurium and Salmonella Stanley isolates in chickens - Razali, Balqis (2018)
The objectives of this study were to determine pathogenicity of Salmonella isolates in chickens and to isolate the agent from the organs. Seventy-six-day-old chicks were divided into three groups namely; group A, inoculated with S. Typhimurium (24 chicks); group B, inoculated with S. Stanley (24 chicks); and group C, was left uninoculated, and acted as the control group (28 chicks). The chicks in groups A and B were inoculated intraperitoneally with 0.1 ml of 1x10⁸ colony forming unit (cfu) of S. Typhimuriumand S. Stanley, respectively at day old. Eight chicks from all groups were separated and monitored for mortality. Chicks were provided with feed and water ad libitum throughout the trial, and monitored for abnormal clinical signs and mortality at least twice daily. Prior to bacterial inoculation, four chicks from group C were sacrificed. On days 1, 4, 7 and 14 post inoculation (pi), four chicks were sacrificed from each group. Body weights and blood samples were collected for detection of Salmonella antibody using ELISA technique prior necropsy. On necropsy, gross lesions were recorded and samples of liver were collected and fixed in 10% buffered formalin for histological examination. Samples of liver, spleen, caecal tonsils and cloacal swabs were collected for bacterial isolation and identification. The study showed that body weight of chickens in all groups increased throughout the trials. There was significant difference (p<0.05) in body weight between groups on day 1 pi, although no significant difference in body weight (p>0.05) on days 4, 7 and 14 pi between groups. Clinical signs seen from a chick in group A on day 8 pi was sudden death meanwhile a chick from group B on day 6 pi was weakness that was found dead on the next day. However, group C showed no abnormal clinical signs throughout the trial. Mortality rate for groups A and B were 12.5% each and none for group C. Necropsy revealed splenomegaly on chicks in group B on days 4, 7 and 14 pi. Nevertheless, no lesion was seen in other groups and the dead chicks. Histology of liver revealed no significant findings in all groups. Salmonella was isolated from group A, on day 1 pifrom spleen (25%) and on day 7 pi from liver (25%), but none on days 4 and 14 pi. However, for group B on day 1 pi Salmonella was isolated from liver (25%) and caecal tonsil (25%); on day 4 pi from liver (50%), caecal tonsil (25%) and also spleen (25%); on day 7 pi from liver (50%), spleen (50%), caecal tonsil (50%), and cloacal swab (50%); but day 14 pi nil. Salmonella was not isolated from group C. Salmonella isolation from dead chicks from group A was from liver, spleen, caecal tonsil and cloacal swab meanwhile, group B was from liver, spleen and caecal tonsil. Salmonella antibody titre declined in all groups throughout the trials. There was no significant difference (p>0.05) in antibody titre between groups on days 1 and 7 pi. However, significant difference (p<0.05) was seen on days 4 and 14 pi. In conclusion, S. Typhimurium and S. Stanley isolates used in the study were pathogenic to chickens as it caused death and gross lesion, and were able to be isolated from the organs. Salmonella Stanley isolate is more pathogenic in chickens when compared to S. Typhimurium.